Between innovation and industrial policy: how Washington succeeds and fails at renewable energy. (1st October 2016) - MacNeil, Robert
Abstract: During its eight years in office, the Obama administration undertook an ambitious effort to transition the US economy towards the use of renewable energy technologies, and promote American leads in the global 'cleantech' industry. While many of the strategies selected to achieve these goals rendered positive results, others proved unproductive and/or politically toxic. Approaching the issue from a critical innovation framework (which focuses on the political and economic conditions under which the federal government is best able to promote technological change), this paper argues that the administration ignored some of the key conditions that have historically allowed Washington to succeed in promoting the uptake of new technologies. The paper describes the nature of these mistakes, and suggests an alternative way forward based on historical precedent.